Forgiveness: It May Be Less About Right and Wrong and More About You and Me - Bassett, Rodney L. (Journal of psychology and christianity, 2018)
This project was designed to test the possibility that one's moral position might predict that individual's disposition to seek or grant forgiveness. Christian college students were given the Moral Foundations Sacredness Scale (MFSS; Graham & Haidt, 2012) which assesses five dimensions of morality designed to be relevant across culture and time. In addition, dispositional inclinations toward granting forgiveness, seeking forgiveness, and self-forgiveness were also assessed. No connection was found between preference for the moral dimensions and dispositional forgiveness. Therefore, a second study was performed testing for the possibility that relational factors might trump moral criteria in regards to forgiveness. The MFSS was administered along with measures of forgiveness, empathy, grace-orientation, and narcissism. As predicted, relational factors were significantly more effective when independently predicting dispositional forgiveness than preferred moral standards.